Pemberitaan Unjuk Rasa Indonesia Gelap di Kompas.com: Analisis dalam Kajian Framing Robert Entman - Fathu Rahman Mujaki; Fakhrur Rozi (Gulawentah:Jurnal Studi Sosial, 2025)
This study analyzes the framing by Kompas.com in reporting the "Dark Indonesia" demonstration that took place on February 17-27, 2025. This study was conducted using a qualitative approach and using Robert Entman's framing analysis. A total of 9 Kompas.com news items were the subjects of the study. The results of the study show that Kompas.com framed the narrative of the "Dark Indonesia" demonstration as a critical action to fight for the aspirations of the people while building moral elements and recommendations for government policies. Kompas.com has a significant role in shaping public opinion while still paying attention to the principles of responsible journalism to ensure the presentation of objective information.